Characterization of Some Electronic Spectral Parameters for Doped Nd(III) Ion in Saturated Aqueous Solution of Some Pharmacetical Compounds - Naulakha, Neelam; Soni, K.P.; Bhati, P.R. (Asian Journal of Chemistry, 2012)
The stereo-environment of doped Nd(III) ion in various saturated solutions of some medicinal compounds has been studied for various electronic spectral parameters. The various electronic parameters, via, Slater Condon (Fk), Lande (z4f), intensity of hypersensitivity band (4G5/2), bonding parameter (b1/2), Judd-Ofelt parameter (Tl) and Racah parameter (Ek) for Nd(III) ion doped in saturated solution of diphenylhydramine, tripelennamine, chlorophenaramine, promethazine, teefinadine, naproxen, fenoprofen, flubiprofen, oxaprozine, ketoprofen and ibuprofen have been studied.